Network analysis reveals potential mechanisms that determine the cellular identity of keratinocytes and corneal epithelial cells through the Hox/Gtl2-Dio3 miRNA axis - Guo, Yanjie; Wu, Weini; Chen, Haoyu; Wang, Xueqi; Zhang, Yi; Li, Shuaipeng; Yang, Xueyi (Frontiers in Cell and Developmental Biology, 2025)
During embryonic development, both corneal epithelial cells (CECs) and keratinocytes (KCs) originate from the surface ectoderm. As a result of this shared origin, corneal epithelial cells may exhibit the same characteristics as the skin epidermis in pathological situations, while keratinocytes are ideal seed cells for tissue-engineered corneas. However, how the identities of keratinocytes and corneal epithelial cells are determined is currently unclear. In this study, to investigate the molecular mechanisms determining the identity of keratinocytes and corneal epithelial cells, small RNA and mRNA sequencing analyses of these two cell types were performed. Analysis of the sequencing data revealed that almost all the miRNAs in the Gtl2-Dio3 imprinting region were highly expressed in keratinocytes and accounted for 30% of all differentially expressed miRNAs (DEMs). Since all the genes in the Gtl2-Dio3 imprinting region form a long polycistronic RNA under the control of the Gtl2 promoter, we next examined the expression of transcription factors and their binding near the Gtl2 locus. The findings indicated that the homeobox family dominated the differentially expressed transcription factors, and almost all Hox genes were silenced in corneal epithelial cells. Transcription binding site prediction and ChIP-seq revealed the binding of Hox proteins near the Gtl2 locus. Analysis of the Gtl-Dio3 miRNA target genes indicated that these miRNAs mainly regulate the Wnt signaling pathway and the PI3K-Akt signaling pathway. The crucial transcription factors in corneal epithelial cells, Pax6, Otx2, and Foxc1, are also targets of Gtl-Dio3 miRNAs. Our study revealed potential mechanisms that determine the cellular identity of keratinocytes and corneal epithelial cells through the Hox/Gtl2-Dio3 miRNA axis, which provides a new perspective for understanding the developmental regulation of corneal epithelial cells and the mechanisms of corneal opacity, as well as for establishing the groundwork for promoting the transdifferentiation of keratinocytes into corneal epithelial cells.